PENGARUH KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI TERHADAP DISIPLIN YANG BERDAMPAK TERHADAP KINERJA KARYAWAN DAN DOSEN - Burhanuddin Burhanuddin; Mohamad Makrus; Wargianto Wargianto (LPPM STIE PERTIBA Pangkalpinang, 2018)
Universities have an important role in producing quality human resources. In order to be able to perform its role well, universities are required to be able to implement good human resource management especially in improving the performance of employees and lectures. This research is intended to analyze the influence of leadership, motivation, and compensation to the discipline that affects the performance of employees and lecturers at the College of Health Science Abdi Nusa Pangkalpinang. The population is all employees and lecturers, amounting to 52 people and because the number is below 100 then the entire population made the respondent. Measurement of research variable with instruments in questionnaires that are quantified by Likert scale. This analytic method uses Path Analysis. Hypothesis testing uses F (simultaneous) and t-test (partial). The result of this research resulted that leadership did not affect the discipline while motivation and compensation respectively partially positively and significantly influence to the discipline, the next discipline influence the performance of employees and lecturers at the College of Health Science Abdi Nusa Pangkalpinang. Recommendation of this research is expected to increase the knowledge of leaders of all areas and institution provide support and awards to improve the performance of employees and lecturers